2022
DOI: 10.55519/jamc-03-9483
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Hepatitis C Antibody Assays and Evaluation of Agreement Between Hepatitis C Antigen and PCR Results

Abstract: Background: Hepatitis C is associated with a wide range of health repercussions. Pakistan is one of the highly prevalent countries of Hepatitis C Virus (HCV) infection. The availability of cost-effective, robust, and reliable screening and diagnostic tests for hepatitis C is important to address the disease burden. Standardization of screening and diagnostic assays in clinical laboratories is crucial for achieving big goals. Objectives of this study are to correlate the results of two different HCV antibody (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…A high correlation between HCV-Ag test and HCV PCR, such as the CAP/CTM test, has been described in the literature (12,21,23,25,26). Similar to Chang, et al (12) and, more recently, to Iqbal, et al (26), who found an excellent correlation (r=0.960 and r=0.950, respectively), our findings showed a strong positive association (r=0.890) between the two tests in all samples with quantifiable viral load, which suggests that the HCV-Ag test may be a good predictor for the identification of clinical cases of active hepatitis C infection.…”
Section: Discussionmentioning
confidence: 89%
“…A high correlation between HCV-Ag test and HCV PCR, such as the CAP/CTM test, has been described in the literature (12,21,23,25,26). Similar to Chang, et al (12) and, more recently, to Iqbal, et al (26), who found an excellent correlation (r=0.960 and r=0.950, respectively), our findings showed a strong positive association (r=0.890) between the two tests in all samples with quantifiable viral load, which suggests that the HCV-Ag test may be a good predictor for the identification of clinical cases of active hepatitis C infection.…”
Section: Discussionmentioning
confidence: 89%